Dynamic Analysis of New Chaotic System with Five Scroll and Two Scroll Attractors: Offset Boosting and Total Amplitude Control, Adaptive Synchronization - Ramar, Rameshbabu; Mohanavel, G. (Journal of Applied Nonlinear Dynamics, 2026)
In this research paper, a new 3-D chaotic system with infinitely many equilibrium points is introduced and analyzed various basic dynamic behaviors such as dissipativity, stability, Lyapunov exponents, etc. The detailed dynamic analysis of the proposed system is conducted using bifurcation, Lyapunov spectrum, and attractor diagram. It is interestingly noted that the proposed system can generate two-scroll, five-scroll, and a real butterfly-like chaotic attractor which can be used to improve the complexity of the system. Some other interesting features such as total amplitude control and offset boosting control also realized in the proposed system for various engineering applications. The numerical calculation and MATLAB simulation results indicate the rich chaotic dynamics in the proposed system. Furthermore, the adaptive synchronization of the proposed system is achieved with unknown system parameters.